Evaluation of Vocational High School Students' Soft Skills During Industrial Internship: A Case Study of Grade XII Chemical Engineering Students at SMKN 3 Mataram - Ahmadi Ahmadi; Baiq Risni Maripa (Indonesian Journal of Applied Science and Technology, 2026)
This study evaluates soft skills, punctuality, discipline, and work ethic among Grade XII students of SMKN 3 Mataram, Industrial Chemical Engineering Department, during an industrial internship at CV. Chemika Karya is a household-product manufacturer producing soaps, detergents, floor cleaners, and related cleaning products. The study used a qualitative evaluative case study involving six male students who were assessed directly by an industrial supervisor. Data were collected from structured observation sheets, a simple workplace assessment rubric, and supervisor evaluation notes. The assessed dimensions were creativity, teamwork, communication, problem-solving, punctuality, discipline, and work ethic. Data were analyzed using simple tools: spreadsheet tabulation to summarize assessment categories, color-coded recapitulation to identify recurring patterns, and a manual thematic matrix to interpret supervisor notes. The findings show that creativity, teamwork, communication, problem-solving, and punctuality were still weak. Students tended to wait for instructions, were not yet confident in proposing ideas, needed guidance in coordinating tasks, and often reported problems only after being asked by the supervisor. Punctuality also required improvement, especially in arriving on time and completing assigned tasks according to schedule. However, work ethic was assessed positively because students showed willingness to learn, respect for workplace procedures, and responsibility for assigned work. These findings suggest that vocational schools need to strengthen pre-internship preparation through work communication drills, collaborative assignments, simple problem-based learning, punctuality habituation, and continuous feedback from industrial supervisors.